2015
DOI: 10.4103/0300-1652.150696
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors for domestic violence among pregnant women in a rural community Northwest, Nigeria

Abstract: Objective:Domestic violence (DV) against women constitutes a violation of human rights. This study aimed at determining the prevalence and predictors for DV among pregnant women in a rural community northwest Nigeria.Materials and Methods:A descriptive cross-sectional study which utilised an interviewer-administered semi-structured pretested questionnaire. This assessed the type of DV experienced, the perpetrators and the trigger factor. Logistic regression analysis was used to assess the relative effect of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 13 publications
7
25
1
Order By: Relevance
“…Out of the overall prevalence of 25.4%, 24.5% was emotional violence, 8.1% was physical violence, and 2.4% was sexual violence. This result (25.4%) is similar to the studies carried out in Uganda (27.7%) [17] and Nigeria (28.3%) [18], but lower compared to the studies carried out in Zimbabwe (61.3%) [19], Rwanda (35.1%) [20], South Africa (31%) [21] Nigeria (34.3%) [22], and Kenya (37%) [23] and the studies conducted in Ethiopia (32.2% [11] and 44.5% [12]). In contrast, the prevalence of domestic violence in this study is higher than in the studies carried out in America (16.8%) [24] and Nigeria (11.6% [25] and 7.4% [26]).…”
Section: Discussionsupporting
confidence: 75%
“…Out of the overall prevalence of 25.4%, 24.5% was emotional violence, 8.1% was physical violence, and 2.4% was sexual violence. This result (25.4%) is similar to the studies carried out in Uganda (27.7%) [17] and Nigeria (28.3%) [18], but lower compared to the studies carried out in Zimbabwe (61.3%) [19], Rwanda (35.1%) [20], South Africa (31%) [21] Nigeria (34.3%) [22], and Kenya (37%) [23] and the studies conducted in Ethiopia (32.2% [11] and 44.5% [12]). In contrast, the prevalence of domestic violence in this study is higher than in the studies carried out in America (16.8%) [24] and Nigeria (11.6% [25] and 7.4% [26]).…”
Section: Discussionsupporting
confidence: 75%
“…This is similar to findings from studies in (Nigeria) 21 , (Ethiopia) 13 and (USA). 23 Finally, the study shows that sociodemographically most of the abused pregnant women were less than 29 years, had lower education, were employed, had higher family monthly income, were Christians, were married, were of Annang/Ibibio/Oron (indigenous) ethnic groups and were of lower parity (para 0-4).Even though only ethnicity was statistically significantly associated with domestic violence, these socio-demographic variables were similar in other studies, 3,17,[31][32][33] and further corroborate the fact that domestic violence against pregnant women cuts across age, educational, social class, religious and ethnic barriers. This calls for a closer look at the issue with the aim of ensuring that all pregnant women presenting for ante-natal care are thoroughly screened for domestic violence.…”
Section: Discussionmentioning
confidence: 61%
“…8,[26][27][28] This finding is however in disagreement with findings from other workers which showed reversal of the order of the violence. 14,15,17,20 The preponderance of physical violence in the study could be due to culture of the people here with predilection to physical violence. Husbands were the commonest culprits in the violence against the pregnant women in the study.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with pregnant women shows that health workers should pay attention to the cases of violence omitted by pregnant women, since many do not report for fear of reprisals (19) . Referring to fear, a survey conducted with health professionals identified that it may be associated with women in situations of violence and health professionals facing the problem (14) .…”
Section: She Does Not Have the Understanding Of What She Is Sufferingmentioning
confidence: 99%
“…In 64.5% the children witnessed the violence and in 17.73% they witnessed and suffered aggressions. The main form of violence reported was physical (31,432), followed by psychological (19,182), moral (4,627), sexual (3,064) and patrimonial (1,382) (3) .…”
Section: Introductionmentioning
confidence: 99%